A high-performance doped photocatalysts for inactivation of total coliforms in superficial waters using different sources of radiation - Claro, Elis Marina Turini [UNESP]; Bidoia, Ederio Dino [UNESP]; de Moraes, Peterson Bueno (Elsevier, 2016)
Photocatalytic water treatment has a currently elevated electricity demand and maintenance costs, but the photocatalytic water treatment may also assist in overcoming the limitations and drawbacks of conventional water treatment processes. Among the Advanced Oxidation Processes, heterogeneous photocatalysis is one of the most widely and efficiently used processes to degrade and/or remove a wide range of polluting compounds. The goal of this work was to find out a highly efficient photocatalytic disinfection process in superficial water with different doped photocatalysts and using three sources of radiation: mercury vapor lamp, solar simulator and UV-A LED. Three doped photocatalysts were prepared, SiZnO, NSiZnO and FNSiZnO. The inactivation efficiency of each synthesized photocatalysts was compared to a TiO2 P25 (Degussa®) 0.5 g L-1 control. Photolysis inactivation efficiency was 85% with UV-A LED, which is considered very high, demanding low electricity consumption in the process, whereas mercury vapor lamp and solar simulator yielded 19% and 13% inactivation efficiency, respectively. The best conditions were found with photocatalysts SiZnO, FNSiZnO and NSiZnO irradiated with UV-A LED, where efficiency exceeded 95% that matched inactivation of coliforms using the same irradiation and photocatalyst TiO2. All photocatalysts showed photocatalytic activity with all three radiation sources able to inactivate total coliforms from river water. The use of UV-A LED as the light source without photocatalyst is very promising, allowing the creation of cost-effective and highly efficient water treatment plants.
Keywords: Disinfection; Heterogeneous photocatalysis; N-doped; Si-doped; Superficial water treatment; UV-A LED